Medición de variaciones espacio - temporales de la temperatura del agua en su interacción superficie y el subsuelo utilizando redes de difracción de Bragg en un tramo de un arroyo de montaña colombiano (2020)
This final master's project presents the optical sensors based on fiber Bragg gratings (FBG) as a possible solution for the measurement of spatiotemporal variations of temperature in hydrological applications. Specifically, it presents a prototype for measuring water temperature variations due to the interaction between the surface and the subsoil in a mountain stream using fiber Bragg gratings. In this document, four arrays of FBG sensor pairs were designed. Their temperature responses were characterized obtaining curves with coefficients of determination above 0.9998 for each of the FBG sensors. Moreover, these FBG sensors were tested under a water column level up to 55 cm. Measurements validated that the designed sensors are insensitive to variations in the level of water up to the limits evaluated in the test. Finally, the prototype measurement system was implemented at 3 different points of interest in a stream located in the mountains of Puente de Boyacá, Boyacá, Colombia. Simultaneous temperature measurements were made for a period of 24 hours. Temperature gradients for each area of interest were obtained as well as the spatiotemporal gradient of water temperature in its interaction between surface and subsoil. The highest gradient with a maximum temperature between surface water and groundwater of 1.4°C was obtained for the arrangement of sensors located in the first position. The maximum temperature gradient for sensor arrays located in the second and third positions was 0.6°C and 0.45°C respectively.